Midlatitude daily summer temperatures reshaped by soil moisture under climate change. Issue 2 (19th January 2016) - Douville, H.; Colin, J.; Krug, E.; Cattiaux, J.; Thao, S.
Abstract: Projected changes in daily temperatures are highly model dependent, particularly in the summer midlatitudes where the spread in the response of heat waves represents a major obstacle for the design of adaptation strategies. Understanding the main reasons for such uncertainties is obviously a research priority. Here we use a set of global atmospheric simulations to assess the contribution of the soil moisture feedback to changes in the full distribution of daily maximum summer temperatures projected in the late 21st century. Results show that this feedback (i) accounts for up to one third of the mean increase in daily maximum temperatures, (ii) dominates changes in the shape of the distribution, and (iii) explains about half of the increase in the severity of heat waves over densely populated areas of the northern midlatitudes. A dedicated intercomparison project is therefore needed to assess and constrain land surface feedbacks in the new generation Earth System Models. Key Points: The soil moisture feedback amplifies the midlatitude summer warming over land The soil moisture feedback dominates changes in the shape of T max distribution The soil moisture feedback can explain half of the increase in heat wave severity